Measuring resilience in a risky world: Why, where, how, and who? - Barrett, Christopher B.; Headey, Derek D. (International Food Policy Research Institute, 2014)
Much of the world’s chronically poor and malnourished population lives in an increasingly volatile world. The dangerous nexus of climate change, rapid population growth, conflict, and economic stagnation has already pushed several poor regions into states of permanent crisis, even as the rest of the world has enjoyed unprecedented progress against poverty.